2013
DOI: 10.1007/s11434-012-5593-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of light rain events over China and the mid-high latitudes of the Northern Hemisphere

Abstract: Based on observed daily precipitation data, monthly gridded radiosonde upper air temperature and sea surface temperature data from the UK Met Office Hadley Centre, monthly surface air temperature from the Climatic Research Unit at the University of East Anglia and the NCEP/NCAR monthly reanalysis data, this study investigates the spatial and temporal variations of light rain events over China and the mid-high latitudes of the Northern Hemisphere during 1961-2010, and discusses the relationship between the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…The work of Qian, et al [23], Fu, et al [34], Huang and Wen [25], and Liu, et al [35] attributed the reduction of light rain days over eastern China to increases in lower-tropospheric temperatures that were capable of one or more of the following: (1) increasing the dew-point temperature; (2) causing a rise in the condensation height of precipitable clouds and reducing cloudage; and (3) weakening atmospheric stability and strengthening upward motion such that precipitation intensity increased and light rain events decreased. Nevertheless, universal increases in lower-tropospheric temperature cannot explain increasing trends in light rain events over western China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Qian, et al [23], Fu, et al [34], Huang and Wen [25], and Liu, et al [35] attributed the reduction of light rain days over eastern China to increases in lower-tropospheric temperatures that were capable of one or more of the following: (1) increasing the dew-point temperature; (2) causing a rise in the condensation height of precipitable clouds and reducing cloudage; and (3) weakening atmospheric stability and strengthening upward motion such that precipitation intensity increased and light rain events decreased. Nevertheless, universal increases in lower-tropospheric temperature cannot explain increasing trends in light rain events over western China.…”
Section: Discussionmentioning
confidence: 99%
“…From 1973 to 2009, decreasing trends for light rain events have been observed in North America, Europe, and Asia, especially in eastern Asia [22]. Previous studies have led researchers to conclude that light precipitation days have significantly decreased over eastern China (east of 100 • E) [8,21,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all of the potential causes for decreases in light precipitation, an increase in lower-tropospheric temperatures is considered to be the main factor. Lower-tropospheric temperature increases the dew-point temperature, causes a rise in the condensation height of precipitable clouds, and reduces cloudiness, weakens atmospheric stability, and strengthens upward motion [28,29,32,34]. A study by Wu et al [33] for eastern China indicated that both lower-tropospheric warming and specific humidity were responsible for variations in light rain days during the warm season.…”
Section: Study Areamentioning
confidence: 99%
“…Light precipitation requires additional time to soak into soils, leaving less water for surface runoff [2], and this characteristic of light precipitation is important for abating droughts in the arid region of Xinjiang. In the past, studies have focused on decreasing light precipitation days over eastern China [28][29][30][31][32][33]. Of all of the potential causes for decreases in light precipitation, an increase in lower-tropospheric temperatures is considered to be the main factor.…”
Section: Introductionmentioning
confidence: 99%